2007
DOI: 10.1144/gsl.sp.2007.270.01.15
|View full text |Cite
|
Sign up to set email alerts
|

A surface-subsurface study of reservoir-scale fracture heterogeneities in Cretaceous carbonates, North Oman

Abstract: Reservoir-scale structural heterogeneity, especially in terms of mechanical layering and natural fracture systems, is often insufficiently constrained by subsurface data alone. In North Oman, a large dataset in Cretaceous carbonates comprises data from multiple subsurface reservoirs and analogue outcrops. This provides an ideal opportunity to integrate outcrop constraints into the subsurface, and to calibrate the resulting models dynamically. For this purpose, a reservoir-scale analogue outcrop fracture templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Cements are nonferroan to ferroan and may contain petroleum inclusions (Videtich et al 1988;de Keijzer et al 2007;; Fig. 9D).…”
Section: Compaction and Cementationmentioning
confidence: 99%
See 3 more Smart Citations
“…Cements are nonferroan to ferroan and may contain petroleum inclusions (Videtich et al 1988;de Keijzer et al 2007;; Fig. 9D).…”
Section: Compaction and Cementationmentioning
confidence: 99%
“…9D). Burchette & Britton (1985), Videtich et al (1988), de Keijzer et al (2007 and Taberner et al (2010) all reported the intergrowth of 'exotic' minerals (principally kaolinite, dickite and fluorite), homogenization temperatures of approximately 80-130(C and/or a trend from light to heavy carbon isotope values within burial diagenetic calcite cements. Rare descriptions of cathodoluminescence characteristics document a non-luminescent to dull to bright luminescence within compositionally zoned crystals, with no apparent intra-zonational corrosion (Cross et al 2010;Taberner et al 2010).…”
Section: Compaction and Cementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fracture networks from outcrop data were first used in water resource management (Long and Billaux, 1987) and fracture modelling from lidar data is common practice in geotechnical fields (Deparis et al, 2008;Gigli and Casagli, 2011;Schulz, 2007). Fracture studies from lidar data are currently been used with increasing frequency in the hydrocarbon industry (Barr et al, 2007;De Keijzer et al, 2007;Gillespie et al, 2010;Kurtzman et al, 2009;Rogers et al, 2007). A Discrete Fracture Network or DFN approach models fluid flow processes through rock masses via a series of connected fractures (Jing and Stephansson, 2007) and requires statistics on size, density, orientation, position, and aperture of the fractures to generate a stochastic model of the fracture network.…”
Section: Fault and Fracture Statisticsmentioning
confidence: 99%